Sihir among contemporary Malays - Azizah Rahmad (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2012)
This study is about black magic (sihir) among contemporary Malays. It provides a historical overview of the relationship between Malays and the practice of black magic to show how it has evolved with the advance of time. The work engages in a wide range of material from contemporary Malay magazines and newspapers, to scholarly research on the Islamic conception of the unseen (ghayb) as well as the observations of Orientalists on magic in Malay culture. Ultimately, this study finds that belief and practice of sihir among contemporary Malays still persist despite the advancement in areas of institutional Islamization and modernization that Malaysia and Malays have experienced over the past three decades. On the contrary, it has evolved into a more sophisticated and technologically updated form since contemporary practitioners of sihir can be found utilizing the media to advertise their services. This study shows that the demand for sihir is purely to involve in covert social ills and the presence of the Islamic healing centres indicate that the belief in and practice of sihir has not subsided. The existence of these Islamic healing centres also does not help contain sihir. This study recommends that in order for the practice of sihir to be completely eradicated, there must be a strong co-operation between the relevant government, Islamic organizations, the learned section of society and all other concerned party to form a 'think-tank' on how to solve this 'cancer' of the race and the necessity for laws to control the practice of sihir.